Immunoturbidimetric assay for estimating free light chains of immunoglobulins in urine and serum. Issue 6 (June 1991) - Tillyer, C R; Iqbal, J; Raymond, J; Gore, M; McIlwain, T J
Abstract : An immunoturbidimetric assay for the assessment of free kappa and lambda light chains of immunoglobulins was developed using a commercial polyclonal antiserum with reactivity towards epitopes on the light chains, which are not expressed when they are bound to heavy chains. The assay, on a centrifugal analyser, is simple and rapid. The limit of detection is 5 mg/l of free light chain, with an assay range of 5-120 mg/l, intrabatch precisions from 1.5-6.4%, and interbatch precisions from 6.5-8.9%. The assay was only slightly less sensitive than colloidal gold staining of cellulose acetate electrophoreses for the detection of Bence-Jones protein in urine. For the serial monitoring of response to chemotherapy in patients with myeloma, the assay correlated well with serum paraprotein estimates obtained by densitometric scanning of Ponceau stained cellulose acetate electrophoreses, but not with serum beta-2 microglobulin measurements, even after correction for the effects of creatinine. These assays may prove to be of use for the monitoring of tumour response in the treatment of Bence-Jones myeloma.